QATAR COUNTRY'S ISLAMIC PROSELYTIZING METHODS AT THE 2022 WORLD CUP - Sartika, Anita; Rosyada, Amrina (QAULAN: Journal of Islamic Communication, 2023)
The 2022 FIFA World Cup is a new historical record for the Islamic world. For the first time since 1930, this most prestigious football match was held in the Islamic country, Qatar. The choice of Qatar as the host in the FIFA executive committee meeting has raised pros and cons since it was announced in 2010. But amid these pros and cons, the various positive reports regarding the 2022 World Cup show that Qatar is preparing its country well. This is also the case with the da'wah of Islam carried out by this country. Qatar is considered successful in spreading Islam rahmatan lil alamin, one of which is through the recitation of Q.s. Al-Hujurat: 13 by Ghanim Al-Muftah during the opening ceremony. Apart from these examples, many other Islamic da'wah will be discussed in this article. In Q.s. An-Nahl: 125, Allah swt. explains the methods of wisdom that can be used in preaching, including wisdom, Al-Mau'idzah al-hasanah, and good rebuttals. This article aims to analyze Qatar's da'wah methods in the 2022 World Cup. The formulation of the problem in this article is how is da'wah with wisdom, Al-Mau'idzah al-hasanah, and good rebuttals made by Qatar? This analysis concludes that the al-mau'idzah al-hasanah method is the most widely applied. In addition, the propaganda method used by Qatar has also succeeded in creating peace, joy, and love for Islam and the state of Qatar.